(untitled) (Architecture Image Studies, 2025)
The popularity of Japanese pop culture in Indonesia has reached the point where it has become part of one’s identity. This phenomenon has catalyzed the emer-gence of Indonesian Vtubers known for its visual representation by the creator. While studies pertaining Vtubers mostly focused on the audience, this study fo-cused more on the creators exploring motivation behind their creative decision. Through in-depth interviews with seven Indonesian Vtubers and questionnaire disseminated through the Vtuber community, we found that Indonesian Vtubers perceive their virtual persona as alter ego. Most of their creative decision is driven by their cultural interest towards Japanese pop culture, this is also based on their cultural background and how they are exposed to Japanese pop culture since childhood to teenager including anime, manga, and games. This study concludes that virtual persona such as Vtuber serves as an extension of one’s self. Vtubing allows the creator to explore identity based on their cultural preferences.